Three Daughters of Eve - "Shafak, Elif" (Penguin Books: London, 2016)
Peri, a wealthy Turkish housewife, is on her way to a dinner party at a seaside mansion in Istanbul when a beggar snatches her handbag. As she wrestles to get it back, a photograph falls to the ground - an old polaroid of three young women and their university professor. A relic from a past - and a love - Peri had tried desperately to forget. The photograph takes Peri back to Oxford University, as an eighteen year old sent abroad for the first time. To her dazzling, rebellious Professor and his life-changing course on God. To her home with her two best friends, Shirin and Mona, and their arguments about Islam and femininity. And finally, to the scandal that tore them all apart
Keywords: Friendship Fiction